2022
DOI: 10.1002/adma.202201315
|View full text |Cite
|
Sign up to set email alerts
|

Strain Modulation for Light‐Stable n–i–p Perovskite/Silicon Tandem Solar Cells

Abstract: Perovskite/silicon tandem solar cells are promising to penetrate photovoltaic market. However, the wide‐bandgap perovskite absorbers used in top‐cell often suffer severe phase segregation under illumination, which restricts the operation lifetime of tandem solar cells. Here, a strain modulation strategy to fabricate light‐stable perovskite/silicon tandem solar cells is reported. By employing adenosine triphosphate, the residual tensile strain in the wide‐bandgap perovskite absorber is successfully converted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 44 publications
0
46
0
Order By: Relevance
“…So far, some mechanisms have been found to explain the thermodynamic driving force for halide segregation, such as compositional/electronic structure-linked free energy difference, polaron formation and strain effect, , bandgap reduction, hole injection and accumulation, local electric field, and anion vacancies, which provide the guidelines for rationally designing materials to solidify the soft perovskite lattice. The mutual principle for all the scenarios is to shut down the ion-to-vacancy or ion-to-ion migration channels by considering the vacancy-assisted migration process, for example, eliminating anion vacancies or lowering dimension with large organic cations. , As evidenced by the recent study on Pb 2+ /Pb 0 and I – /I 3 – redox chemistry, the iodide ions suffer from grain-to-boundary diffusion and then nucleate at grain boundaries to form an iodide-rich phase .…”
mentioning
confidence: 99%
“…So far, some mechanisms have been found to explain the thermodynamic driving force for halide segregation, such as compositional/electronic structure-linked free energy difference, polaron formation and strain effect, , bandgap reduction, hole injection and accumulation, local electric field, and anion vacancies, which provide the guidelines for rationally designing materials to solidify the soft perovskite lattice. The mutual principle for all the scenarios is to shut down the ion-to-vacancy or ion-to-ion migration channels by considering the vacancy-assisted migration process, for example, eliminating anion vacancies or lowering dimension with large organic cations. , As evidenced by the recent study on Pb 2+ /Pb 0 and I – /I 3 – redox chemistry, the iodide ions suffer from grain-to-boundary diffusion and then nucleate at grain boundaries to form an iodide-rich phase .…”
mentioning
confidence: 99%
“…3d. Recent studies have well illustrated that the residual tensile strain in a perovskite film leads to instability, 40–42 and hence releasing the lattice strain by PDCBT also enhances the perovskite film stability.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the peak intensity and position, it was observed that the peak width was broadened in perovskite film after bending or folding, due to that the iodine‐rich segregations and microstrain created by atomic displacement. [ 27,28 ] Additionally, Figure 5d displays the change of steady‐state photoluminescence (PL) of perovskite films subjected to different strains. It can be seen that the larger the strain value, the lower is the PL intensity, indicating the more the nonradiative recombination centers.…”
Section: Resultsmentioning
confidence: 99%